ANALYSIS OF K-POP FANS DRIVERS IN PURCHASING MERCHANDISE ON ONLINE GROUP BUYING (GROUP ORDER). - Qadri, Rizni Aulia; Sinambella, Fitriana Aidnilla; Arafah, Nadiya Nur (Universitas Lancang Kuning, 2024)
This study was conducted with the aim of analyzing the driving factors of K-Pop fans in purchasing merchandise on online group buying suc as Group Order (GO). The population of this study is K-Pop fans in Indonesia and the sample of this study is K-Pop fans who have purchased merchandise on Group Order (GO). This study uses quantitative research methods and collects data using an online survey. This study uses Partial Least Square (PLS) analysis with the SmartPLS3 application as a data analysis method. The results of this study found that K-Pop, Impulsive Buying, Customer Perceived Value have a significant positive effect on Purchase Intention. Then Perceived Trust and Perceived Price Fairness have no significant effect on Purchase Intention, and Purchase Intention has a significant positive effect on Actual Purchase Behavior.